Urban navigations : politics, space and the city in South Asia - Anjaria, Jonathan Shapiro; McFarlane, Colin, 1979- (New Delhi : Routledge, 2011)
Contributed articles.
pt. I. Contested landscapes -- pt. II. Infrastructures and materialities -- pt. III. Imagining the urban.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: City and town life -- South Asia; Cities and towns -- South Asia -- Social conditions; Urbanization -- South Asia; Electronic books